O sujeito psicótico e sua posição em relação ao laço social: as contribuições de Jacques Lacan até o período do Seminário III - As Psicoses (1955-1956) - Pereti, Leonardo Zanelli (2011)
The present research intends to construct the concept of the psychotic subject up to the Seminar III The psychoses (1955-1959) of Jacques Lacan, French psychoanalyst who proposed a new way to think the subject matter. As notorious follower of Freud, Lacan started from the progress and impasse made by the psychoanalysis creator in this field. Freud's main contribution is on thinking that the psychosis is not only a pathology and that it is another way of psychic organization. Nevertheless, Freud did not idealize a clinical treatment for the psychoses, but he did not desist from producing a theory about the issue, in private on some articles and on his study about the book Memoirs of My ervous Illness by Daniel Schreber. Lacan, still affiliated with psychiatry, on his doctoral thesis On Paranoia and Its Relationship to Personality (1932), starts from the concept that there would be a human sense in psychosis which had been left aside by the psychiatry and that it would be necessary to retake this concept, thinking the psychogenesis dimension of paranoia symptoms. Affiliated with psychoanalysis, Lacan formulates the hypothesis that in psychosis there would be a foreclosure of a primordial signifier, what would lead to another organization of the symbolic register. Based on Freud and searching for the human sense, Lacan brought from the surrealistic movement and from philosophy, that the dimension of the subject in psychosis is the bet which allows it to be seen over and above psychiatric dungeons. Finally, we propose that the movements of effort for the inclusion of the psychotic should take into account the dimension of the subject in psychosis, because they should participate actively in their treatment. Therefore, the exit would be to think the dimension of the subject and its particularity in the case of psychosis, after all he made his choice for this structure. We concluded, herewith, that retaking these psychosis theory fundamental concepts allows a contribution to the efforts for social inclusion of the psychotic subject